(untitled) (Hoboken, N.J., 2007)
Network Security provides the latest research and addresses likely future developments in network security protocols, architectures, policy, and implementations. It covers a wide range of topics dealing with network security, including secure routing, designing firewalls, mobile agent security, Bluetooth security, wireless sensor networks, securing digital content, and much more.
Ứng dụng công nghệ thông tin trong dạy học Sinh học
Keywords: Computer networks,Mạng máy tính; Security measures; Biện pháp an ninh